Saints in the Christian Tradition: Unraveling the Canonization Process - Gribble, C.S.C., Richard (Studies in Christian-Jewish Relations, 2011)
Contemporary people, both Christian and non-Christian like, find the Roman Catholic process of declaring saints, known as canonization, to be both interesting and mystifying. This essay seeks to unravel the apparent mystery by providing a historical chronicle that describes the development and evolution of this process. Beginning in the Patristic Church, when persecution was normative, martyrs to the faith were exalted by local peoples and with time declared saints. Later, when martyrdoms subsided greatly, men and women who demonstrated "heroic virtue" were placed on a par with martyrs and also declared saints. By the late medieval period, after some abuses in the declaration of saints were noted, the process of canonization became more centralized in the office of the Pope. Processes to determine heroic virtue and to verify miracles, which became a necessary element to both beatification and canonization, were also developed. By the time of the early 20th century and the formalization of Canon Law in 1917, a rigorous process to declare men and women as saints was present. In the post-Vatican II era, this process has been streamlined and become more formalized through documents published by Popes John Paul II and Benedict XVI.